The power of power in supplier-retailer relationships - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2005)
In his interesting paper, Martin Hingley makes a few key observations about power and role accorded to it in the relationship marketing literature that has become increasingly popular over the past decade. Fundamentally, the article states that the relationship marketing view sees power as alien to effective relationships, as negating cooperation, and as the antithesis of trust. In other words, power in a relationship is ‘‘only viewed in a negative sense’’. Or, alternatively, power is viewed as not important enough to include in relationship marketing models because firms have moved from transactional exchanges to relational exchange. It is contended by the relationship marketing literature that as adversarial and arms-length dealings have been replaced by close partnerships and long-term commitments, power (especially power imbalance) has no place in these latter type of relationships. The article quotes my research as supporting some of these conclusions. In this paper I will argue that my conclusions about power in channel relationships are a bit more nuanced than the above description. And, my view of power is actually sympathetic of Hingley’s main thesis that power is central to channel relationships and that effective partnerships have both cooperative (positive-sum) and competitive (zero-sum) dimensions. Furthermore, despite central tendencies favouring the rise of trust and commitment under conditions of high mutual dependence, it is possible to see trusting relationships associated with asymmetric power structures.